O desafio da universalização do abastecimento de água e esgotamento sanitário em Minas Gerais: considerações a partir da política estadual de saneamento (2004-2014) - Siqueira, Lauren Fernandes de (2016)
Access to basic sanitation is vital to achieve some of the social rights mentioned in the Brazilian Constitution of 1988. This is closely linked to the achievement of the rights to health and housing. Although accessing basic sanitation services is a recognized social right, its universalization still represents a major challenge in Brazil, especially in rural and poor areas of its cities. Financing difficulties, technical and institutional constraints are factors that prevent the universal coverage of water supply and sanitation in various Brazilian regions. Given that the government plays a central role in promoting access to basic sanitation, especially in the less economically developed towns, this work examines the challenge implied in promoting universalization of water supply and sanitation in Brazil, taking as analytical reference the state of Minas Gerais. To accomplish this goal it will be analyzed the effort undertaken by the state government, through sectoral policies implemented from 2004 to 2014. The analysis of the institutional framework and the model of provision of water supply and sanitation services in this state allows to state that the regulation of the sanitation policy has not been able to impose directions to the stakeholders responsible for universalizing the provision of these services.